2017
DOI: 10.1007/s00024-017-1545-7
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Lunar Month Periods Observed in Natural Neutron Flux at High Altitude

Abstract: Air radon concentration measurement is useful for research on geophysical effects, but it is strongly sensitive to site geology and many geophysical and microclimatic processes such as wind, ventilation, air humidity and so * Corresponding author: Xinhua Ma, Key Laboratory of Particle Astrophysics, Institute of High energy Physics, Chinese Academy of Sciences, P.O.Box 918(3), Yuquan Road 19(B), Beijing 100049, China E-mail: maxh@ihep.ac.cn 1 on that induce very big fluctuations on the concentration of radon in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…We found that variations in the measured neutron counts on the order of 10% were observed when the moisture changed from 100% saturated to 94% saturated. (Stenkin et al, 2017) measured the effect of the seasonal rainfall on thermal neutron count rates indoors high elevation, finding that the ground-moisture effect on the count rate should be ~10%. This effect is not, however, included in the model prediction of the neutron count rate vs. atmospheric pressure or elevation.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that variations in the measured neutron counts on the order of 10% were observed when the moisture changed from 100% saturated to 94% saturated. (Stenkin et al, 2017) measured the effect of the seasonal rainfall on thermal neutron count rates indoors high elevation, finding that the ground-moisture effect on the count rate should be ~10%. This effect is not, however, included in the model prediction of the neutron count rate vs. atmospheric pressure or elevation.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…We found that variations in the measured neutron counts on the order of 10% were observed when the moisture changed from 100% saturated to 94% saturated. (Stenkin et al, 2017) measured the effect of the seasonal rainfall on thermal neutron count rates indoors high elevation,…”
Section: Thermal and Epithermal-to-fast Neutronsmentioning
confidence: 99%
See 1 more Smart Citation
“…The existence of periodical variations both seasonal and related to the moon month are confirmed for the first time at high altitude. In particular, for synodic moon month the 4th harmonic with amplitude of about 0.5% and maximum with a delay of about 1 day after syzygies is found [12]. It indicates that the EN-detectors can be used to monitor seismic activity.…”
Section: Introductionmentioning
confidence: 90%
“…Mao-Yuan Liu Sun-Moon-Earth system [9] and earthquakes [10], which can periodically changes thermal neutron flux.…”
Section: Study Of the En-detectors Array In Tibetmentioning
confidence: 99%